Insights into Ruthenium(II/IV)‐Catalyzed Distal C−H Oxygenation by Weak Coordination. Issue 69 (29th October 2020) - Bu, Qingqing; Kuniyil, Rositha; Shen, Zhigao; Gońka, Elżbieta; Ackermann, Lutz
Abstract: C−H hydroxylation of aryl acetamides and alkyl phenylacetyl esters was accomplished via challenging distal weak O‐ coordination by versatile ruthenium(II/IV) catalysis. The ruthenium(II)‐catalyzed C−H oxygenation of aryl acetamides proceeded through C−H activation, ruthenium(II/IV) oxidation and reductive elimination, thus providing step‐economical access to valuable phenols. The p ‐cymene‐ruthenium(II/IV) manifold was established by detailed experimental and DFT‐computational studies. Abstract : C−H hydroxylation of aryl acetamides and alkyl phenylacetyl esters is achieved via a challenging distal weak O ‐coordination by a ruthenium(II/IV) catalyst. The process includes C−H activation, ruthenium(II/IV) oxidation and reductive elimination which provides step‐economical access to valuable phenols.